Phenotypic and Agronomic Variation Within Naturalized Medicago polymorpha L. (Burr Medic) in Subtropical Queensland, Australia, and Relationships with Climate and Soil Characteristics - David L. Lloyd; John P. Thompson; Suzanne P. Boschma; Rick R. Young; Brian Johnson; Kemp C. Teasdale (Agronomy)
To characterize the naturalized population of burr medic (Medicago polymorpha L.), a valuable pasture legume, in subtropical Queensland, Australia, a collection of 1747 lines from 107 sites in 11 regions was grown, and 26 phenotypic and agronomic attributes were recorded. This data matrix was analyzed by cluster, principal co-ordinates, discriminant and correlation analyses to examine line relationships based on plant attributes and their association with site characteristics of climate and soil. Among the wide polymorphism of attributes across the collection zone, there were a number of notable phenotypic associations. One of these, with large green leaves, minimally dentate leaf margins, and light purple petioles, was widely distributed. Three others, one with a distinctive magenta leaf mark, dark purple petioles, and an upright habit; one with those same attributes but with a prostrate habit; and one with grey-green leaves, high frost resistance, and the ability to stay green and to produce high pod yields, were associated with climatic and soil characteristics in the north, east, and south of the collection zone, respectively. Days to flowering were longer in lines from saline soils at lower altitude, and plant vigor was greatest in lines from more fertile soils with higher rainfall. A wide variation in time to flower of lines at all collection sites contributes to the adaptation of M. polymorpha in subtropical Queensland and potentially to its persistence with future climate change.